Added Value of Dual-Energy CT in COVID-19 Pneumopathy. Issue 1 (21st October 2021) - Deprez, Louis; Boulanger, Yves-Gauthier; Guiot, Julien
Teaching point: The use of dual-energy instead of conventional single-energy computed tomography pulmonary angiogram can provide additional value concerning the diagnosis of COVID-19 and its complications, especially in the detection of small pulmonary embolism.